Pelvic Ring Reconstruction with an Osteocutaneous Fibula Flap for Abdominal Wall Repair in Adults with Bladder Exstrophy - Pedro Alvedro-Ruiz; Alberto Sánchez-García; Iván Heredia-Alcalde; Belén Andresen-Lorca; Ana Trapero-Ovejero; Miriam Alonso-Carpio; Providencia García-Pastor; Salvador Pous-Serrano; Alberto Pérez-García (Indian Journal of Plastic Surgery)
Abdominal wall repair in adults with bladder exstrophy is challenging. We present a case of a 46-year-old woman with bladder exstrophy presenting with a large midline incisional hernia associated with a 13-cm hypoplasia of both pubic rami that precluded fixation of any abdominal mesh. A two-stage approach was adopted. First, a free vascularized osteocutaneous fibula flap was used to reconstruct the pelvic ring. After complete bone union 18 months later, a mesh was anchored to the fibula flap to restore the abdominal wall competence. After 2 years of follow-up, no hernia recurrence was observed, and the patient reported improved quality of life and self-esteem. This novel technique may provide long-term stability and good functional outcomes for reconstruction of the abdominal wall in selected adults with bladder exstrophy.